DDEL-12. QUADRUPLE CARBON DOT NANO MODEL FOR ENHANCED TUMOR TARGETING AND DUAL DRUG DELIVERY FOR THE TREATMENT OF PEDIATRIC HIGH-GRADE GLIOMAS. (14th November 2022) - Graham, Regina; Cilinger, Emel Kirbas; Hettiarachchi, Sajini; Zhou, Yiqun; Ferreira, Braulio; Leblanc, Roger; Vanni, Steven
Abstract: High-grade gliomas remain among the most lethal neoplasms. Nanotechnology aims to Improve drug targeting and efficacy. Here we developed a quadruple nano-model (QNM) that specifically targets pediatric high-grade glioma cells and delivers chemotherapies to the cell nucleus. This carbon dot based QNM were fabricated by covalently attaching two drugs (epirubicin and temozolomide) and two targeting peptides. ShPep-1 peptide binds to the IL-13Rα2 receptors allowing for cellular import while lnPep-1h peptide delivers the DNA damaging drugs to the nucleus. Despite demonstrating the lowest measurable drug content (23.3%), the dual peptide linked QNM induced significantly greater cell death than single peptide linked conjugates suggesting enhanced cell uptake. Greatest effect was observed in glioblastoma (SJ-GBM2) and diffuse intrinsic pontine glioma (NP53) cells with IC50s of approximately 60 nM, 3-6-fold lower than single peptide conjugates. Imaging studies using FITC-conjugated carbon dots confirmed the dual peptide conjugate demonstrated greatest cellular uptake and nuclear localization.